The effect of socioeconomic activities on solid waste generation : a case study in South Johore, Malaysia - Mohd. Razman Salim; Ahmad Tarmizi Abd. Karim; Fadil Othman; Sabarinah Marzuky; International Conference on Solid Waste Management (9th : 1993 : Philadelphia, PA USA)
09